Digital Transformation and Organizational Support on Employee Performance: The Mediating Role of Individual Readiness for Change - Baidowi, Mofid; Paminto, Ardi; Adhimursandi, Doddy (Islamic University of Kalimantan MAB Banjarmasin, 2026)
This study aims to analyze the effect of digital transformation and organizational support on employee performance with individual readiness for change as a mediating variable at PT Migas Mandiri Pratama East Kalimantan. The research uses a quantitative approach with survey method. The study population is all 70 permanent employees using census sampling technique. Data collection uses questionnaires with 5-point Likert scale. Data analysis uses Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that digital transformation has a positive and significant effect on employee performance, while organizational support has no significant direct effect on employee performance. Both digital transformation and organizational support have positive and significant effects on individual readiness for change. Individual readiness for change has a positive and significant effect on employee performance with the largest effect size among all relationships. Furthermore, individual readiness for change partially mediates the relationship between digital transformation and employee performance, and fully mediates the relationship between organizational support and employee performance. These findings emphasize the critical role of individual readiness for change as a mechanism bridging organizational initiatives with employee performance outcomes.